Respostas

A melhor resposta!
2014-04-23T18:40:39-03:00
\frac { 2 }{ x^2-9 } \ge \frac { 1 }{ x-3 } \\ \\ x^2-9=(x-3)(x+3)\\ \\ \frac { 2 }{ (x-3)(x+3) } -\frac { 1 }{ (x+3)(x-3) } \ge 0\\ \\ \frac { 2-1(x+3) }{ (x-3)(x+3) } \ge 0\\ \\ \frac { 2-x-3 }{ x^2-9 } \ge 0\\ \\ \frac { -x-5 }{ x^2-9 } \ge 0\\ \\ \\

Raizes\\ -x-5=0\\ -x=5\quad (-1)\\ x=-5\\ \\ x^2-9=0\\ x^2=9\\ x=\sqrt { 9 } \\ x\pm 3



++++++(-5)-----------------------------------------
++++++++++++++(-3)--------------3-------------
++++++(-5)--------(-3)+++++++++3++++++++

S=]-\infty ,-5]U]-3,3[
2 5 2